(untitled) (Educational Dimension, 2022)
In this paper, an algorithm for adaptive testing of students’ knowledge in distance learning is proposed, along with an assessment of its effectiveness in the educational process. The paper provides an overview of the results of modern test theory application, a description and block diagram of the proposed algorithm, and the results of its application in the real educational process. The effectiveness of using this algorithm for objectively assessing students’ knowledge has been demonstrated experimentally.